How confident are general practitioners in interpreting neuroradiology reports?. Issue 11 (November 2018) - Currie, S.; Saunders, D.; Khoshneviszadeh, S.; Craven, I.
Abstract : Aim: To determine the level of confidence general practitioners (GPs) have in radiology reports provided by neuroradiologists and to elicit the preferences of GPs regarding report format and level of detail. Materials and methods: Electronic surveys comprising anonymised neuroradiology reports were sent to GP practices served by a tertiary neuroscience centre. After reviewing the reports, GPs were asked to complete a two-part questionnaire. Firstly, GPs indicated their level of confidence, using a five-tiered Likert scale, in their understanding of: (a) the body of text; (b) the meaning of the report; and (c) the significance of the report. Secondly, GPs provided free-text suggestions for improving the report and highlighted any phrases that they did not understand. Results: One hundred GPs responded from a group of 439 that received a survey (response rate 23%). Although the majority of GPs were fairly confident in their understanding of reports, fewer than one-third of GPs were entirely confident. Approximately 10% of GPs were not confident at all in their understanding of the reports. Causes of confusion included the use of detailed anatomy, acronyms, radiological terminology, and a lack of a conclusion and an action plan. Conclusion: General practice is a time-sensitive discipline that demands clear communication. In neuroradiology reports, GPs do not find detailed anatomy, acronyms, or radiological terminology helpful. Rather, GPs want a clear conclusion and action plan. Highlights: 10% of GPs do not feel confident interpreting neuroradiology reports. GPs desire concise neuroradiology reports with clear subheadings. All neuroradiology reports should have a separate conclusion lacking jargon. Where possible radiology reports should 'signpost' the clinician toward further management. GPs find advice regarding a timeframe for recommended management very helpful.